DOI: 10.31274/etd-180810-1735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fast pyrolysis biochar on physical and chemical properties of a sandy soil

Abstract: Ames, Iowa 2012 ii To: My father, my mother and my sister, who always give me all the support and love that I need (Translation: para mi padre, mi madre y mi hermana quienes siempre me dan todo el soporte y amor que necesito)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
(97 reference statements)
1
6
1
Order By: Relevance
“…In addition, tillage is a pivotal factor in moisture loss; investigators would do well to compare surface broadcast with tilled biochar (Gaskin et al, 2010). Basso (2012) found greater water retention in deep-banded compared with mixed topsoil-biochar, where loss to drainage exemplified by changes in hydraulics were evident. On the other hand, due to the use of containers without drainage holes, our retention percentages for all samples were elevated due to limitations on subsurface evaporation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, tillage is a pivotal factor in moisture loss; investigators would do well to compare surface broadcast with tilled biochar (Gaskin et al, 2010). Basso (2012) found greater water retention in deep-banded compared with mixed topsoil-biochar, where loss to drainage exemplified by changes in hydraulics were evident. On the other hand, due to the use of containers without drainage holes, our retention percentages for all samples were elevated due to limitations on subsurface evaporation.…”
Section: Discussionmentioning
confidence: 99%
“…CEC increases were modest except in the case of silty loam where we inferred 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim www.plant-soil.com priming effects (Tammeorg et al, 2014). Selected oak and cardboard biochar properties were compared to selected indices reported for oak biochar by Basso (2012) and for cardboard biochar by Mitchell et al (2013).…”
Section: Biochar and Blended Soil Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Individual ions did not always follow this pattern of increasing amount extracted with increasing HCl concentration, but the majority of exceptions to this pattern had relatively high coefficients of variation (>25%) (Figures 3.4 and 3.6a). The relative amounts of K, Ca, and Mg released from the RO and CS biochars by 0.05M HCl were similar to the relative concentrations of these elements measured by ultimate analysis of similarly produced red oak and corn stover biochars (Basso, 2012;Brewer et al, 2009) were similar to or slightly lower than total P and S contents reported in the literature for RO and CS biochars (Brewer et al, 2011;Brewer et al, 2009;.…”
Section: Ion Releasesupporting
confidence: 78%
“…The RO biochar had an ash content about half that of CS biochar, and the CE biochar had negligible ash content. However, the ash contents of the RO and CS biochars were only about half of what has been reported in the literature (Basso, 2012;Brewer et al, 2009). The difference is attributed to the sieving of the biochars that was performed in this study but not in other studies.…”
Section: Ash Content and Solubilitycontrasting
confidence: 69%